High intensity focused electromagnetic therapy evaluated by magnetic resonance imaging: Safety and efficacy study of a dual tissue effect based non‐invasive abdominal body shaping - Kinney, Brian M.; Lozanova, Paula (Lasers in surgery and medicine, 2019)
Objectives This study introduces an initial evaluation of a novel High‐Intensity Focused Electromagnetic (HIFEM) technology. The primary goal is to quantify any effects the treatments may have on abdominal tissues, as well as to establish hypotheses for future research of this technology. Methods Twenty‐two patients received four abdominal treatments using the EMSCULPT device (BTL Industries Inc., Boston, MA). Anthropometric evaluations were recorded and digital photographs were taken at baseline, at 2 months, and at 6 months post‐treatments. The MRI without contrast determined by vertertebras T12 and S1 (FIESTA and FSPRG sequences) was used to measure dimensions in coronal cross‐sectional images of abdominal muscle and fatty tissues, in order to assess any anatomical changes induced by the application. Results Analysis of the same MRI slices verified by tissue artefacts showed a statistically significant (all P < 0.0001) average 18.6% reduction of adipose tissue thickness, 15.4% increase in rectus abdominis muscle thickness, and 10.4% reduction in rectus abdominus separation (diastasis recti) as measured from the medial border of the muscle 2 months post‐treatment. More significant improvements were observed in patients with BMI 18.5–24.9 (classified as “normal”). MRI data from 6‐month follow‐up suggest the changes can be preserved in longer term. Tape measurements showed on average 3.8 cm subumbilical circumference reduction. The weight of the subjects did not change significantly (average −0.5 lb; P > 0.05). No adverse events were reported. Conclusions MRI, considered as a highly precise diagnostic method, revealed simultaneous muscle growth, fat reduction and reduced abdominal separation at 2 months and at 6 months post treatments, unrelated with dieting. Further research should investigate the exact physiological processes which stand behind the tissue changes observed in this study. Lasers Surg. Med. 51:40–46, 2019. © 2018 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.